The communicative status of topic recontextualization - Kovalchuk, Liudmyla V. (Східноєвропейський національний університет імені Лесі Українки, 2018)
The article presents the study of the communicative status of topic recontextualization in the discourse. The study of context is realized in its organic connection with an object of the speaker’s thought or a topic which makes it possible to reveal the cognitive structure of context and to analyze deeply the communicative status of recontextualization. Recontextualization is defined as a linguo-cognitive operation aimed at functional topic reorientation in the discourse caused by the change of interlocutors’ perspective on the topic. The communicative status of topic recontextualization includes various communicative factors: spatio-temporal inhomogeneity, redistribution of communicative roles, side-participant presence and polytopicality of communication. Special attention is focused on the study of the lingual means that contribute greatly to topic recontextualization in the discourse.
Keywords: topic; recontextualization; context models; communicative factors; lingual means